2018
DOI: 10.1589/jpts.30.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-week lumbar stabilization exercise and sling exercise on lumbosacral region angle, lumbar muscle strength, and pain scale of patients with chronic low back pain

Abstract: [Purpose] The purpose of this study is to investigate the effects of lumbar stabilization exercise and sling exercise on lumbosacral region angle, lumbar muscle strength, pain scale of patients with chronic low back pain. [Subjects and Methods] The subjects of this study were 29 chronic low back pain patient women who were selected among participants in exercise class at K Region Health Promotion Center in South Korea and were randomly assigned to the lumbar stabilization exercise group (n=10), sling exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
2
35
1
1
Order By: Relevance
“…All included studies adopted a randomised controlled design (RCT). The main inclusion criterion was (chronic) non-specific low back pain ≥ 4 weeks 22 , ≥ 6 weeks 23 , ≥ 7 weeks 24 , ≥ 8 weeks [25][26][27] , ≥ 12 weeks , ≥ 24 weeks [56][57][58] and ≥ 2 year history 59 , whilst in 11 [60][61][62][63][64][65][66][67][68][69][70] studies this information was not presented. The baseline pain, effect sizes (Cohen's d, stabilisation exercise group only) for pain and disability are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included studies adopted a randomised controlled design (RCT). The main inclusion criterion was (chronic) non-specific low back pain ≥ 4 weeks 22 , ≥ 6 weeks 23 , ≥ 7 weeks 24 , ≥ 8 weeks [25][26][27] , ≥ 12 weeks , ≥ 24 weeks [56][57][58] and ≥ 2 year history 59 , whilst in 11 [60][61][62][63][64][65][66][67][68][69][70] studies this information was not presented. The baseline pain, effect sizes (Cohen's d, stabilisation exercise group only) for pain and disability are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, only 23 22,25,28,[30][31][32][33][34][35][38][39][40][41]43,45,[49][50][51]53,54,56,58,63,[67][68][69][70][71] studies reported on the number of repetitions per set per exercise, with a range of 6 23,24,26,27,36,38,42,44,[46][47][48][50][51][52]55,57,[59][60][61][64][65][66]69 to 30 66 repetitions (mean: 13.6 ± 5.6 repetition...…”
Section: Study Quality and Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Chronic low back pain (CLBP) is a global health problem with high incidence, and it is often very detrimental to health, thereby causing substantial economic losses to society [1][2][3]. Studies have confirmed that lumbar back muscle strength [4] and lumbar lordosis angle [5] are of great importance in maintaining the stability of the lumbar spine. Furthermore, decline in the strength of trunk muscles and increase or decrease in lumbar lordosis angle are related to CLBP [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Daugiau kaip 80% darbingų žmonių bent vieną kartą gyvenime patiria nugaros skausmus, o 18% populiacijos dėl apatinio nugaros dalies skausmo kenčia dažnai (Vujcis et al, 2018). Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 1 (18) 2018, 32-41;ISSN 2029-3194 / eISSN 2538 Skirtingų kineziterapijos programų poveikis asmenų, jaučiančių lėtinį nespecifinį apatinės nugaros dalies skausmą, liemens funkcinei būklei ir skausmui Esant lėtiniam nespecifiniam apatinės nugaros dalies skausmui, dažnai taikomi stuburo stabilizavimo pratimai, kineziterapija vandenyje ir šiaurietiškasis ėjimas (Irandoust, Taheri, 2015;Revord et al, 2016;Ko et al, 2018). Visų šių trijų kineziterapijos metodų naudą asmenų, jaučiančių lėtinį nespecifinį apatinės nugaros dalies skausmą, nugaros skausmo mažinimui, liemens funkcinės būklės gerinimui įrodė daugelis mokslininkų (Irandoust, Taheri, 2015;Revord et al, 2016;Li et al, 2017;Ko et al, 2018).…”
Section: įVadasunclassified